Case-control study of activities associated with SARS-CoV-2 infection in an adult unvaccinated population and overview of societal COVID-19 epidemic counter measures in Denmark. - Pernille Kold Munch; Laura Espenhain; Christian Holm Hansen; Tyra Grove Krause; Steen Ethelberg (PLoS ONE)
Measures to restrict physical inter-personal contact in the community have been widely implemented during the COVID-19 pandemic. We studied determinants for infection with SARS-CoV-2 with the aim of informing future public health measures. We conducted a national matched case-control study among unvaccinated not previously infected adults aged 18-49 years. Cases were selected among those testing positive for SARS-CoV-2 by RT-PCR over a five-day period in June 2021. Controls were selected from the national population register and were individually matched on age, sex and municipality of residence. Cases and controls were interviewed via telephone about contact with other persons and exposures in the community. We determined matched odds ratios (mORs) and 95% confidence intervals (95%CIs) by conditional logistical regression with adjustment for household size and immigration status. For reference, we provide a timeline of non-pharmaceutical interventions in place in Denmark from February 2020 to March 2022. We included 500 cases and 529 controls. We found that having had contact with another individual with a known infection was the main determinant for SARS-CoV-2 infection: reporting close contact with an infected person who either had or did not have symptoms resulted in mORs of 20 (95%CI:9.8-39) and 8.5 (95%CI 4.5-16) respectively. Community exposures were generally not associated with disease; several exposures were negatively associated. Consumption of alcohol in restaurants or cafés, aOR = 2.3 (95%CI:1.3-4.2) and possibly attending fitness centers, mOR = 1.4 (95%CI:1.0-2.0) were weakly associated with SARS-CoV-2 infection. Apart from these two factors, no community activities were more common amongst cases under the community restrictions in place during the study. The strongest risk factor for transmission was contact to an infected person. Results were in agreement with findings of our similar study conducted six month earlier.